CAPITAL SOCIAL, PRECARIZAÇÃO E UBERIZAÇÃO DO TRABALHO - Ana Christina Tavares Martins; Maria Geralda de Miranda (TRF2, 2017)
In this fast study the relations between social capital, organization of work, precariousness, outsourcing, sharing economy and the uberization of relations by the formation of new options for the market and for the worker are examined. Will be analyzed if the entrance of 'dot com' companies and the acting through the apps (e-hailing) really bring more freedom, autonomy and better earnings for the individual workers or if the better profit and the advantages still in the hands of the companies. Will be verified the quantum of the social capital the worker put or not in this 'new' work relation form, if bosses still exist ou not in this virtual market.